2001
DOI: 10.1046/j.1365-2303.2001.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of primary lymphoma of the thyroid: a report of 17 cases

Abstract: Between 1980 and 1998, 4272 thyroid surgical specimens with a preoperative fine needle aspirate were sent to our Anatomical Pathology Department. Among these cases there were 17 primary thyroid lymphomas, which constituted 0.3% of all the thyroid lesions and 2.3% of the thyroid malignancies. Seven cases were diffuse large B-cell (DLBC) lymphomas and 10 were MALT lymphomas. Of the DLBC lymphomas six were correctly diagnosed by fine needle aspiration cytology (FNAC) and one was diagnosed as positive for malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 13 publications
2
80
0
Order By: Relevance
“…However, the results of FNAC for the diagnosis of thyroid lymphoma are inconsistent, and its diagnostic accuracy varies widely [7][8][9][10][11]. Sangalli et al reported that FNAC was successful in detecting lymphoma in 76% of cases, and no false-positive cases were found [9].…”
Section: Clinical Characteristics and Treatment Modalities Of Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of FNAC for the diagnosis of thyroid lymphoma are inconsistent, and its diagnostic accuracy varies widely [7][8][9][10][11]. Sangalli et al reported that FNAC was successful in detecting lymphoma in 76% of cases, and no false-positive cases were found [9].…”
Section: Clinical Characteristics and Treatment Modalities Of Patientmentioning
confidence: 99%
“…However, three of ten patients with MALT lymphoma (30%) were erroneously diagnosed as Hashimoto's thyroiditis, although the other seven patients were diagnosed as or suspected of lymphoma. Therefore, they concluded that the diagnosis of high-grade thyroid lymphoma was fairly easy based on cytomorphological features, and found that immunocytochemistry can be used to confirm suspicious cases [9]. Differentiation of primary thyroid lymphoma from Hashimoto's thyroiditis using FNAC may be difficult, especially when the thyroid lymphoma is of low-grade histology such as MALT lymphoma.…”
Section: Clinical Outcome and Comparison Of The Clinical Characteristmentioning
confidence: 99%
“…Primary thyroid lymphoma (PTL) is a rare cause of malignancy, accounting for <5%of thyroid malignancies [45] and < 2% of extra-nodal lymphomas [46,47], with an annual estimated incidence of 2 per 1 million [48]. Women are more commonly affected than men (2-8:1) [47,49,50].…”
Section: Hashimoto's Thyroiditis and Thyroid Lymphomamentioning
confidence: 99%
“…A fine-needle aspiration biopsy (FNAB) is recommended as the first -line diagnostic procedure, but owing to its low sensitivity and specificity, a core needle biopsy or open surgical biopsy is often necessary. 10 Since the histopathological diagnostic workup is time -consuming, some patients have to be treated before establishing a definite diagnosis. Tracheal compression may be relieved surgically or conservatively, usually with corticosteroids.…”
mentioning
confidence: 99%